2021
DOI: 10.1186/s12951-021-00934-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel CD44-targeting and pH/redox-dual-stimuli-responsive core–shell nanoparticles loading triptolide combats breast cancer growth and lung metastasis

Abstract: Background The toxicity and inefficient delivery of triptolide (TPL) in tumor therapy have greatly limited the clinical application. Thus, we fabricated a CD44-targeting and tumor microenvironment pH/redox-sensitive nanosystem composed of hyaluronic acid-vitamin E succinate and poly (β-amino esters) (PBAEss) polymers to enhance the TPL-mediated suppression of breast cancer proliferation and lung metastasis. Results The generated TPL nanoparticles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Responsive probes associated with a single molecule are easy to emit “false positive” signals, while probes activated by two or more pathological changes make the imaging precise and become more attractive ( Table 1 and Figure 16 - 18 ) 102 , 134 - 141 . An activatable NIR-II nanoprobe HISSNPs was developed, which responds to dual-pathological-parameter to control the fluorescence condition for tumor imaging.…”
Section: Dually-activatable Probesmentioning
confidence: 99%
“…Responsive probes associated with a single molecule are easy to emit “false positive” signals, while probes activated by two or more pathological changes make the imaging precise and become more attractive ( Table 1 and Figure 16 - 18 ) 102 , 134 - 141 . An activatable NIR-II nanoprobe HISSNPs was developed, which responds to dual-pathological-parameter to control the fluorescence condition for tumor imaging.…”
Section: Dually-activatable Probesmentioning
confidence: 99%
“…[ [116][117][118][119][120][121][122] PEG-PEI-GEM polyethylenimine-graft-poly(ethylene glycol)gemcitabine pH Light…”
Section: Combination Of Various Stimuli For Polymersmentioning
confidence: 99%
“…Because redox reactions and differences in pH occur naturally in the body, these two stimuli are very appealing for drug delivery applications [133]. These types of polymers have been created for a myriad of applications, such as enhancing drug delivery and tumor cell uptake, creating a faster drug release rate within the cytoplasm and nucleus, and further stabilizing the stability of nanoparticles in vivo [116,133].…”
Section: Ph/redox-responsive Polymersmentioning
confidence: 99%
“…In order to improve the tumor delivery rate and anti-metastatic effect of chemotherapy, Zhang et al designed a CD44-targeting and pH/redox-sensitive nanosystem, which can actively target CD44 overexpressed on the cell surface through hyaluronic acid and release the drug in response to the tumor microenvironment, improving the antitumor effect. At the same time, lung metastasis of tumor was inhibited [ 142 ]. The results in vitro and in vivo indicated that the preparation had good effect on promoting tumor cell apoptosis and anti-tumor metastasis.…”
Section: Tdds For Tpmentioning
confidence: 99%